Streptococcus pyogenes-associated facial infection with orbital involvement: a spectrum analysis of cases based on clinical course - Karaś-Marczak, Alicja; Kokot, Witold; Długońska, Agnieszka; Kokot, Aleksandra (Klinika Oczna / Acta Ophthalmologica Polonica, 2025)
This article aims to present the diagnostic and treatment process for patients with rapidly progressing inflammation of the facial soft tissues, most often caused by group A β-hemolytic streptococci, with particular emphasis on the observed ophthalmological complications. The primary goal is to demonstrate the rationale behind therapeutic decisions and interventions, highlighting their consequences and underscoring the need for prompt surgical intervention in cases of necrotizing tissue inflammation. Inflammation of the facial soft tissues extending beyond the orbital septum involves the periorbital space and the bony boundaries of the orbit. This clinical condition carries a risk of severe complications affecting the eye. The article examines five medical cases observed at St. Adalbert’s Hospital in Gdansk during 2022/2023. The cases presented differ in the severity of disease progression − ranging from mild inflammation to rapidly advancing optic nerve damage, resulting in permanent monocular vision loss.